2022
DOI: 10.5409/wjcp.v11.i4.375
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sports participation on cardiovascular health markers of children and adolescents: Systematic review and meta-analysis

Abstract: BACKGROUND Cardiovascular diseases have a high prevalence in adults and their development begins in the first decades of life. On the other hand, sports participation in childhood and adolescence provides benefits which can delay the onset of these diseases. AIM To synthesize the available literature on the impact of sports participation on cardiovascular outcomes in children and adolescents. METHODS This systematic review was conducted on st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Regardless, given the recent rise in discussion about CTE among the public, the generally accepted facts about CTE should be more widely discussed with TBI patients and sports athletes to decrease misinformation from spreading. Sports participation has many benefits, including its promotion of cardiovascular health (23), role as a protective factor against anxiety and depression (24), and provision of access to social support; as such, plummeting sports participation due to this misinformation should be of heightened concern. It is recommended that clinicians actively work to dispel myths related to CTE by facilitating this conversation with patients when appropriate ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, given the recent rise in discussion about CTE among the public, the generally accepted facts about CTE should be more widely discussed with TBI patients and sports athletes to decrease misinformation from spreading. Sports participation has many benefits, including its promotion of cardiovascular health (23), role as a protective factor against anxiety and depression (24), and provision of access to social support; as such, plummeting sports participation due to this misinformation should be of heightened concern. It is recommended that clinicians actively work to dispel myths related to CTE by facilitating this conversation with patients when appropriate ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible hypothesis for the inverse association between early sports practice and hypertension is that the practice of sports provides health improvements which can be tracked along the life stages. A recent systematic review reported that sports participation promotes benefits to cardiovascular structure and function in adolescence [ 3 ] . In addition, sports are the most intense physical activities practiced during this life stage [ 1 ], being associated with better physical fitness [ 15 18 ], which is an important factor for cardiovascular health and prevention of hypertension [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sports practice in childhood and adolescence has been considered a protective factor for a series of cardiovascular risk factors. In fact, a recent meta-analysis [ 3 ] showed that children and adolescents who participate in sports present better cardiovascular structure and function compared to those who do not participate, such as lower blood pressure values and carotid intimal thickness. In addition, original studies have shown that participation in sports is associated with better glucose values [ 4 ] and heart rate variability [ 5 ], dyslipidemias [ 6 , 7 ], and cardiac autonomic modulation [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…28 Further, a recent systematic review on the impact of youth sport participation on CVD health markers found sport participation to promote benefits to cardiovascular structure and function; however, only six studies met the restrictive inclusion criteria with two studies of intima-media thickness and four of blood pressure. 29 To complicate the lack of clarity in the relationship between youth sport participation and CVD-risk factors, it is unclear whether there are outcome differences between racial and ethnic groups. Studies that highlight race are rare, as the majority of research has been conducted primarily in white participants.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%